Fiscal Multipliers and Transition Countries - Marić, Željko (Oeconomica Jadertina, 2017)
Bosnia and Herzegovina is in a state of long-term recession. Under these conditions, the State would have to apply the Keynesian economic policy instead of the neoclassical free market policy. This means that the State should take on the role of the main driver of economic development by increasing public spending and the fiscal consolidation. In doing so, it is very important to understand and evaluate the fiscal multipliers, as the successful application of the Keynesian policy depends exclusively on them. The aim of this paper is, after conducting an analysis of determinants and limitations of the fiscal multipliers within the conditions present in transition countries, to provide guidance on how to conduct the public spending policy, together with the monetary policy and structural reforms which would reduce the possible limitations regarding the effect of fiscal multipliers, thus increasing their impact on economic development. The analysis will be conducted on the example of Bosnia and Herzegovina.
Keywords: public spending multiplier; tax multiplier; extrusion effect; incentive effect; transition country